2004
DOI: 10.1071/sr03065
|View full text |Cite
|
Sign up to set email alerts
|

Scattered paddock trees, litter chemistry, and surface soil properties in pastures of the New England Tablelands, New South Wales

Abstract: Scattered paddock trees are widespread throughout rural Australia but their effect on soil conditions has received only limited research attention. This study investigated the influence of 3 Eucalyptus species on surface soil properties on different parent materials at both stocked and unstocked sites on the Northern Tablelands of New South Wales. Mineral soil samples to a depth of 5 cm were collected at intervals up to twice the canopy radius away from tree trunks and litter samples were collected at correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…The observed patterns of litter loads under isolated tree crowns may have important consequences for nutrient cycling and habitat in scattered tree ecosystems. The higher surface foliar litter densities under canopies that normally correlates positively with higher nutrient recapitalization from the tree is in agreement with observations by many scientists [17,40,41].…”
Section: Quantity and Nutrient Composition Of Litter Of The Farmer Pesupporting
confidence: 79%
“…The observed patterns of litter loads under isolated tree crowns may have important consequences for nutrient cycling and habitat in scattered tree ecosystems. The higher surface foliar litter densities under canopies that normally correlates positively with higher nutrient recapitalization from the tree is in agreement with observations by many scientists [17,40,41].…”
Section: Quantity and Nutrient Composition Of Litter Of The Farmer Pesupporting
confidence: 79%
“…Secondly, there were significant declines in soluble Ca 2+ , K + and Mg 2+ , pH, EC and available P with increasing distance from the trees, patterns which have been observed elsewhere (e.g. Wilson et al, 2002;Graham et al, 2004). However, no clearly-defined patterns were apparent with distance from the tree trunk for C, N and S. Thirdly, apart from pH which exhibited an initial decline to 10 cm and then a rapid increase, the concentration of nutrients generally declined with depth in the soil profile ( Figure 4).…”
Section: Discussionmentioning
confidence: 70%
“…Belsky, 1994;Deans et al, 1999;Scholes, 1990), there are relatively few data from the temperate box woodlands of eastern Australia (see however Graham et al, 2004;Wilson et al, 2002). The present study aims to understand more about the impact of trees growing in clumps and isolated trees on surrounding soils.…”
Section: Introductionmentioning
confidence: 96%
“…Thinning stands either maintained, or improved, soil C, N, S, and extractable P relative to dense or un-colonised plots. Across a range of environments, soil nutrients have been found in higher concentrations in the zone around trees relative to adjacent pasture or ground-storey vegetation (e.g., Ryan and McGarity 1983;Belsky et al 1993a, b;Dean et al 1999;Wilson 2002;Graham et al 2004;Wilson and Lemon 2004) and our results suggest that this is so even for stands of C. glaucophylla. Therefore, the retention of this species in the landscape can create local 'environmental improvements' (Ozolins et al 2001).…”
Section: Discussionmentioning
confidence: 46%
“…Noble and Randall (1999) suggested that the effects of plant litter on surface soils might depend on the ash alkalinity of the litter. The C. glaucophylla litter might therefore have quality such that it causes surface acidification in a similar fashion to that observed for Eucalyptus caliginosa on the Table-lands of NSW (Graham et al 2004).…”
Section: Discussionmentioning
confidence: 82%